Efektivitas Penggunaan Permainan Olahraga Bocce dalam Pembelajaran Penjas pada Siswa Tunagrahita: Systematic Literature Review - Fazari, Bariq Sozza; Komariyah, Lilis; Rahmat, Alit; Carsiwan, Carsiwan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
This study aims to determine the effectiveness of the use of bocce sports games used in PE learning for students with disabilities using the systematic literature review (SLR) method. The database used to search for available literature is Google Scholar. The search for articles in this study is limited to publications in the last 10 years published in accredited national journals that can be accessed openly (open access). The subjects in this study were students with disabilities. The results of data identification state that the use of bocce sports games for tunagrahita students is considered effective because through bocce sports games students are more free to move because it does not require thought and is very light to play. In addition, it was found that through bocce sports games, students with disabilities can effectively improve motor skills and social interaction and increase learning interest to be active in PE learning. Keyword : Adaptive Physical Education, Bocce, Intellectual Disabilities